A case report of ultrasound-guided knee nerve pulse radiofrequency combined with platelet-rich plasma in the treatment of knee osteoarthritis. Issue 51 (23rd December 2021) - Jin, Hui; Zuo, Hao; Xu, Rui; Ji, Youbo; Wang, Zhonghan
Abstract: Rationable: Knee osteoarthritis (KOA) is a disease characterized by noninflammatory degenerative changes of articular cartilage. The main clinical manifestations are joint pain and stiffness. Pulsed radiofrequency (PRF) is thought to treat pain by destroying nerve tissue and changing the physical characteristics of nerve tissue membrane. Patient concerns: The patients presents with joint pain and tenderness. Touching around the knee joint will induce pain and joint stiffness when the hand is pressed hard. Interventions: Four patients with knee osteoarthritis underwent pulsed radiofrequency thermocoagulation in the knee joint cavity under ultrasound guidance and injected 2 mL of 10 mg/mL platelet-rich plasma into the joint cavity once a week for a total of 4 times. Record the patient's Visual Analogue Scale (VAS) score and the degree of knee movement limitation before treatment, 1, 3, and 6 months after treatment. Diagnoses: Four patients with knee osteoarthritis. Outcomes: After treatment, the patient's VAS score improved, and the knee joint mobility function recovered well. Ultrasound-guided knee nerve pulse radiofrequency combined with intra-articular injection of platelet-rich plasma can effectively improve the knee joint function and reduce the pain of the patient. The clinical effect is significant, and it is worthy of clinical application.